Scenario of Poverty in Nepal - Upreti, Rochana (Aadim Journal of Multidisciplinary Research, 2025)
Poverty is a multidimensional issue that demands multidimensional solutions. While significant progress has been made, millions continue to suffer from deprivation. Addressing poverty requires a blend of sound economic policies, targeted social programs, and a global commitment to equity and justice. Only through a deep understanding of both its conceptual foundations and empirical manifestations can effective and enduring solutions be crafted.